Legal Protection for Child Victims of Crime Sexual - Sahrani, Nanda; Abbas, Ilham; Djanggih, Hardianto (HORIZON PUBLIC LEGAL STUDIES, 2025)
The purpose of this study is to find out how to analyze legal protection efforts for child victims of sexual crimes as well as preventive efforts by the police in reducing the number of cases of child victims of sexual crimes in the South Sulawesi regional police. This research is included in the category of empirical legal research, where this research is carried out by accumulating data by direct interviews with the research object, which is supported by legal materials and using qualitative data analysis methods. The results of this study show that legal protection for children victims of sexual crimes in the South Sulawesi Regional Police has not been optimally implemented, although there are several efforts such as an empathetic reporting process, assistance by the police, and collaboration with LPSK, the establishment of a special unit, a sexual violence prevention program in schools, and a rehabilitation program, but these efforts have not gone well. Although there have been various preventive measures, cases of sexual violence against children are still high, indicating the need for increased education and more effective protection policies. The recommendations given by the author are that it is hoped that increased training of investigators to handle sexual crimes against children, strengthen collaboration with related institutions, and expand the socialization of children's rights, and regular monitoring of protection programs also needs to be carried out.